Resilience measurement and dynamic evolution of China’s provincial financial infrastructure - Li, Guijun; Xiong, Zhongwei; Kou, Chenhuan; Li, Shanshan (Frontiers in Physics, 2025)
Financial infrastructure provides a fundamental guarantee for the sound and efficient operation of financial markets. This paper constructs a provincial-level financial infrastructure resilience evaluation index system, measures the level of financial infrastructure resilience of 31 provinces in China from 2005 to 2020, reveals the dynamic evolution characteristics of financial infrastructure resilience in the spatial and temporal dimensions, and analyzes the barrier factors affecting the dynamic change of financial infrastructure resilience level. The results of the study show that: Provincial financial infrastructure resilience level overall upward trend, in which resilience of risk and control is in a stagnant growth state, resilience of recovery and stability, resilience of transformation and development is on the rise; The level of financial infrastructure resilience and the rate of change generally show a spatial distribution trend of “low west and high east, north-south concave,” with the “wooden barrel effect” evident in the eastern region; Provincial financial infrastructure resilience is in the medium-low coupling stage, affected by the spillover effect is prone to form a “club convergence” phenomenon; The industrial structure, shadow banking risk, real estate liability risk, and fintech level are the main barrier factors to the resilience of financial infrastructure, resilience of risk and control, resilience of recovery and stability and resilience of transformation and development’s barrier degree respectively show a rising, declining, stable trend of change. Therefore, the follow-up should promote the coordinated development of regional finance and form a regional financial development pattern with staggered development and distinctive features; prevent the risks of regional financial infrastructure; and enhance the resilience of risk and control and the resilience of transformation and development.